Ղրիմի նշանավոր գրիչ Նատերի՝ ընտանեկան կարևոր մի դրվագի ճշգրտման փորձ - Չատյան, Գոհար
One of the most important figures of the Armenian manuscript centre in Crimea was the famous scribe Nater, along with his family. Nater was already an experienced scribe when he migrated with his family from the Armenian province of Baberd to the Crimean city of Surkhat in the early 1340s. There, he continued his activities, teaching the art of writing to his sons and grandchildren as well. Many colophons of manuscripts copied by the members of this family and containing details pertaining to them have come down to us. The article examines an important event in the history of Nater’s family, the episcopal ordination of the scribe’s youngest son Grigor, and attempts to clarify its date. It is concluded that the ordination did not take place in 1358, as previously supposed, but rather in 1362. The establishment of such chronological details not only assists in defining the biography of a particular individual, but also allows us to better reconstruct the history of an entire milieu: in this case dates, places and many other circumstances relating to Armenian manuscript copying in Crimea. Одним из важнейших действующих лиц армянского центра книгописания в Крыму был известный писец Натер со своей семьей. Натер уже опытным писцом, в начале 40-е гг. XIV века вместе со своей семьей мигрирует из армянской провинции Баберд в крымский город Сурхат. Там он продолжает свою многогранную деятельность, обучая рукописному искусству своих сыновей и внуков. Сохранилось множество колофонов рукописей, переписанных членами этой семьи, содержащие подробности их биографий. В статье рассмотрено важное для семьи событие – рукоположение млад- шего сына Натера, Григора, в епископы. Выясняется, что рукоположение имело место не в 1358 г., как предполагалось ранее, а скорее в 1362 г. Подобные поправки очень важны не только для установления биографических деталей, но и часто способствуют уточнению даты, места и других обстоятельств копирования рукописей.
Keywords: Ձեռագրական մշակույթ